Peningkatan Kualitas Sistem Informasi Berbasis Website untuk Kendaraan Listrik Otonom - Septiyanti, Riska Yucha; Satyawan, Arief Suryadi; Siswanti, Sri Desy (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2022)
Current technological developments have made the website a means of disseminating information that offers various conveniences and speeds in its presentation. Speed and convenience are positive values of the existence of the internet. The website is more easily accessible by people in various regions just by using the internet. One of the benefits of the website is that in terms of marketing the products of a business, the website can be a means of promoting, marketing and conveying information effectively and efficiently to the public. Another benefit of website technology is for information purposes of autonomous electric vehicles. This technology in the future can be integrated on the website for the purpose of information on its existence and condition. In fact, it is possible to create applications for the use of autonomous electric vehicles by making calls through the website, as is the case with applications that are currently popular, namely Gojek or Grab.In designing a website-based information system, a markup language consisting of HTML and CSS is used which is synchronized so that it can run simultaneously, besides that, the PHP programming language is also used to make the website look more dynamic and responsive. The method used in improving the quality of the website- based information system for autonomous electric vehicles is the static website method. On static websites the content provided is constant or does not change and on each page is made with HTML code.In this study, a website-based information system was developed for the purposes of a simple autonomous electric vehicle, which operates in the Nurtanio University Bandung campus. This website design consists of 8 pages. Page 1 contains a homepage where general information on research activities for the development of simple autonomous electric vehicles is found. Page 2 contains object detection which displays more detailed information about the object detection technology used in autonomous electric vehicles. Information about the presence of autonomous electric vehicles in the campus environment is then shown on page 3, namely Av Tracker. Page 4 contains the results of the research that has been done. Page 5 contains research opportunities. This website design is also equipped with a contributor page on page 6 which contains researchers involved in autonomous electric vehicle research. Page 7 contains biodata of alumni who have contributed. At the end, page 8 is for contact information for those who are interested in communicating further about matters related to this research.The final form of a website-based information system is to provide convenience to convey information about autonomous electric vehicles, and also to provide convenience for website management according to the required data and for further development with a tracking system.